Combining Path Analysis and X‐Ray Absorption Spectroscopy to Unravel the Zn Sorption Mechanism on Soils. Issue 4 (2nd August 2018) - Fan, Ting-Ting; Cui, Pei-Xin; Sun, Qian; Zhou, Dong-Mei; Alves, Marcelo Eduardo; Wang, Yu-Jun
Abstract : Core Ideas: pH, clay content, and FeDCB played direct roles in Zn adsorption. Zinc sorption on alkaline soils was higher than on acidic soils as a result of the formation of Zn‐precipitate. Clay content affected Zn sorption on soils via FeDCB and cation exchange capacity. Zinc accumulation in soils due to increasing industrial activities can change this plant nutrient into a pollutant. Soil properties significantly affect the sorption and bioavailability of Zn in soils. Twenty‐one soils with different characteristics were collected from the Jiangsu Province, China, to ascertain the effect of soil properties on Zn sorption. A combination of path analysis and x‐ray absorption spectroscopy (XAS) was conducted to elucidate the sorption mechanism of Zn on soils. The results of XAS indicated that Zn sorption on alkaline soils was higher than on acidic soils because of the formation of a Zn‐precipitate [Zn‐Al layered double hydroxide (LDH), ZnCO3, and Zn(HO)2 –2ZnCO3 ]. Although cation exchange is involved, it was not the primary mechanism of Zn sorption on soils. The correlation and path analysis indicated that pH, clay content, and dithionite‐citrate‐bicarbonate extractable Fe (FeDCB ) played direct roles in Zn sorption, in which pH was the dominant factor. The clay content affected Zn sorption on soils measured via FeDCB and cation exchange capacity (CEC) based on the indirect coefficient. The high proportion of Zn‐clay minerals (Zn‐kaolinite, Zn‐illite, Zn‐montmorillonite, and Zn‐vermiculite) further illustrated that soil clay content was the primary factor affecting Zn sorption on soils.